Spatial Characteristics Analysis of Cuiwei Historical Area Based on Depthmap Theory - Junzhang Chen (Formosa Journal of Sustainable Research, 2022)
Although people can walk out of Cuiwei village, they are always in a confused state, and it is difficult to grasp the spatial form of the whole area. Taking Cuiwei village in Qianshan, Zhuhai as an example, based on the theory of spatial syntax, this paper analyzes the integration degree of ancient village vision and the spatial characteristics of historical location, the understandability degree and integration degree of village vision, the control value of vision and the spatial characteristics of historical location, and puts forward relevant suggestions for the future renewal of villages.